UHMWPE textiles and composites. Issue 4 (29th August 2022) - Nawaz Khan, Ashraf; Gupta, Mohit; Mahajan, Puneet; Das, Apurba; Alagirusamy, R.
Abstract: Ultra-high molecular weight polyethylene (UHMWPE) has the potential to make a significant contribution to the efforts currently being made to help to protect the environment by reducing carbon emissions through the substitution of heavy conventional materials with lightweight polymeric materials. Used on its own, UHMWPE also offers complete recyclability with thermoplastic matrices. UHMWPE fibre-based composites (both thermoplastic and thermoset) offer a wide range of applications in various fields such as military protective suits, automotive, aerospace, electronics hardware, tribological application, and biomaterial implants, and this issue of Textile Progress explores the behaviour of UHMWPE with different matrix systems for various purposes. UHMWPE is widely used in the development of ballistic protective armours. Apart from applications where impact resistance is a key requirement, UHMWPE-based composites are currently being employed in the fields such as biomedical implants, anti-friction systems, dielectric and acoustic applications, and other structural fields; the UHMWPE should be extractable from the thermoplastic types and be able to be recycled. The various manufacturing techniques employed in the preparation of UHMWPE and its composites are discussed as are improvements aimed at eradicating existing processing issues associated with UHMWPE.